The lncRNA HOTAIR regulates autophagy and affects lipopolysaccharide‐induced acute lung injury through the miR‐17‐5p/ATG2/ATG7/ATG16 axis. Issue 16 (27th June 2021) - Li, Yujun; Liang, Zhike; He, Hua; Huang, Xiaomei; Mo, Zexun; Tan, Jinwen; Guo, Weihong; Zhao, Ziwen; Wei, Shuquan
Abstract: Long non‐coding ribonucleic acids (lncRNAs) play critical roles in acute lung injury (ALI). We aimed to explore the involvement of lncRNA HOX transcript antisense intergenic ribonucleic acid (HOTAIR) in regulating autophagy in lipopolysaccharide (LPS)‐induced ALI. We obtained 1289 differentially expressed lncRNAs or messenger RNAs (mRNAs) via microarray analysis. HOTAIR was significantly upregulated in the LPS stimulation experimental group. HOTAIR knockdown (si‐HOTAIR) promoted cell proliferation in LPS‐stimulated A549 and BEAS‐2B cells, suppressing the protein expression of autophagy marker light chain 3B and Beclin‐1. Inhibition of HOTAIR suppressed LPS‐induced cell autophagy, apoptosis and arrested cells in the G0/G1 phase prior to S phase entry. Further, si‐HOTAIR alleviated LPS‐induced lung injury in vivo. We predicted the micro‐ribonucleic acid miR‐17‐5p to target HOTAIR and confirmed this via RNA pull‐down and dual luciferase reporter assays. miR‐17‐5p inhibitor treatment reversed the HOTAIR‐mediated effects on autophagy, apoptosis, cell proliferation and cell cycle. Finally, we predicted autophagy‐related genes (ATGs) ATG2, ATG7 and ATG16 as targets of miR‐17‐5p, which reversed their HOTAIR‐mediated protein upregulation in LPS‐stimulated A549 and BEAS‐2B cells. Taken together, our results indicate that HOTAIR regulated apoptosis, the cell cycle, proliferation and autophagy through the miR‐17‐5p/ ATG2 / ATG7 / ATG16 axis, thus driving LPS‐induced ALI.